STRATEGI INOVATIF UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SD DI GAG PAPUA BARAT DAYA PERSPEKTIF MAHASISWA PMM - Anisa (Indonesian Journal of Elementary Education (IJETE), 2025)
Abstract his study aims to analyze teachers’ strategies in implementing the Contextual Teaching and Learning (CTL) approach to improve the quality of learning at Southwest Papua, as well as to examine the contribution of students from the Independent Student Exchange Program (PMM) in supporting the process. The research method employed is a literature review using the Publish or Perish application.The findings indicate that teachers play a crucial role in planning, implementing, and managing classrooms through contextual strategies that connect learning materials with the local environment and students’ real-life experiences. The application of CTL has been proven to enhance students’ motivation, active participation, and learning outcomes. In addition, PMM students provide practical suggestions such as the use of interactive methods including small group discussions, collective reflection, and projects based on everyday experiences. Keywords: Teacher Strategies, Learning Quality, Elementary School. Penelitian ini bertujuan untuk menganalisis strategi guru dalam menerapkan pendekatan Contextual Teaching and Learning (CTL) guna meningkatkan kualitas pembelajaran di Papua Barat Daya, serta meninjau kontribusi mahasiswa Program Pertukaran Mahasiswa Merdeka (PMM) dalam mendukung proses tersebut. Metode penelitian menggunakan kajian literatur (literature review) dengan menggunakan Publish or Perish. Hasil penelitian menunjukkan bahwa guru berperan penting dalam merencanakan, melaksanakan, dan mengelola kelas dengan strategi kontekstual yang mengaitkan materi ajar dengan lingkungan lokal dan pengalaman nyata siswa. Penerapan CTL terbukti meningkatkan motivasi, partisipasi aktif, serta hasil belajar siswa. Selain itu, mahasiswa PMM memberikan saran praktis berupa penggunaan metode interaktif seperti diskusi kelompok kecil, refleksi bersama, dan proyek berbasis pengalaman sehari-hari. Kata Kunci: Strategi Guru, Kualitas Pembelajaran, Sekolah Dasar